Production of biosurfactants (rhamnolipids) by pseudomonas aeruginosa isolated from Colombian sludges - Díaz M., M. P.; Pimienta R., A. L.; Carvajal S., F. G.; Grosso V., J. L. (CT&F - Ciencia, Tecnología y Futuro, 1997)
The biosurfactant production by strains of Pseudomonas aeruginosa isolated from Colombian hydrocarbon contaminated sludges has been determined. The methodology included the isolation of microorganisms, standardization of batch culture conditions for good surfactant production and characterization of the produced rhamnolipid. Several carbon sources were evaluated with regard to the growth and production curves. The stability of the rhamnolipid was also determined under variable conditions of pH, temperature and salt concentration. The strain Pseudomonas aeruginosa BS 3 showed biosurfactant production capabilities of rhamnolipid resulting in concentrations up to 2 g-dm-3 with surface tensions of 30 -32 mN-m-1 in batch cultures with commercial nutrients.